The self-assembly of polypeptides and their hydrolase-like activity - Kok, Vanice Yu Qi (Nanyang Technological University, 2022)
This project intends to investigate the relationship between the self-assembly and hydrolase-like activity of polypeptide poly(lysine)n-b-poly(leucine)m (KmLn). Various types of KmLn polypeptide were explored using acetates such as p-nitrophenyl acetate and 4-nitrophenyl butyrate were investigated as well. The polypeptides were made inhouse before diluting them at different concentrations. UV-Vis spectroscopy was then used to monitor the production rate at which the enzymes would be statured with the substrate for a specific amount of time within the mixture. After that, the data would be transferred to a program, Origin Labs, to decipher the data and understand the enzyme-catalysed reactions using Michaelis-Menten kinetics. The results obtained shows that the production rate and enzyme affinity for each type of acetates used varies greatly. Further modification and improvement on the polypeptides were mentioned to further explore and encourage research based on this project.